A Survey-Based Descriptive Study on Students’ Adoption of IoT-Based Financial Management Tools - Najib, Muhammad Irsyad Naqiuddin Mohd; Noralzlan, Muhammad Adha Mohd Amin; Hozeir, Haslina Hazriq; Gani, Akbar Naldi; Krishnan, Tevitra Gopal; Farid, Nik Ahmad Farys Bin Ahmad; Amir, Aliana Shazma; Isa, Evawaynie Valquis Md. (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2025)
This study presents a survey-based descriptive quantitative analysis of students’ adoption of Internet of Things (IoT)-based financial management tools, particularly smart wallets and budgeting applications, among university students in Malaysia and China. Conducted at Universiti Malaysia Perlis (UniMAP), Campus Cyberjaya, the study examines students’ perceptions of usefulness, ease of use, trust, and behavioral outcomes related to IoT financial tools. Data were collected from 15 respondents using a structured questionnaire and analyzed through descriptive statistics, including mean, median, and mode. Findings indicate that students widely agree IoT-based tools enhance financial planning, saving habits, and overall money management. The results demonstrate strong confidence and increasing comfort in integrating IoT applications into daily financial routines. Supported by the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT), the study contributes to digital inclusion and supports SDG 8 and SDG 9 by promoting responsible financial behavior and technological innovation.